2006
DOI: 10.1017/s0022029906001695
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus pesticides residues in Italian raw milk

Abstract: Organophosphorus pesticides (OPPs), widely used in agriculture, can cause toxic effects to humans and animals. The main purpose of the present work was to determine the contamination in raw milk by the main organophosphorus pesticides used in Italy and to evaluate the opportunity to start specific procedures of risk management along the milk production chain. The samples, collected in 4 Italian dairy plants directly from the tank trucks during the delivering, were representative of 920 tonnes of raw milk. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 4 publications
(5 reference statements)
1
23
1
5
Order By: Relevance
“…This may be related to the imposition of ban/restriction on use of DDT and technical hexachlorocyclohexane (HCH) (α-, β-, γ-and δ-isomers) and increasing use of OPs and SPs groups as a replacement for persistent OCPs (Government of India, Ministry of Agriculture & Farmers Welfare, 2015) which is indicated by the occurrence of OPs and SPs even in human breast milk (Feo et al, 2012;Bedi et al, 2013). Similarly, the presence of OPs residues in bovine milk has already been reported by Pagliuca et al (2006) and Bedi et al (2015) and is mainly attributed to the ability of OPs to covalently link with milk proteins. Cheema et al (2004) have also reported the presence of chlorpyrifos in 6.7% of milk samples collected from Punjab (India), and concentrations in all of these samples exceeded MRL values.…”
Section: Discussionmentioning
confidence: 91%
“…This may be related to the imposition of ban/restriction on use of DDT and technical hexachlorocyclohexane (HCH) (α-, β-, γ-and δ-isomers) and increasing use of OPs and SPs groups as a replacement for persistent OCPs (Government of India, Ministry of Agriculture & Farmers Welfare, 2015) which is indicated by the occurrence of OPs and SPs even in human breast milk (Feo et al, 2012;Bedi et al, 2013). Similarly, the presence of OPs residues in bovine milk has already been reported by Pagliuca et al (2006) and Bedi et al (2015) and is mainly attributed to the ability of OPs to covalently link with milk proteins. Cheema et al (2004) have also reported the presence of chlorpyrifos in 6.7% of milk samples collected from Punjab (India), and concentrations in all of these samples exceeded MRL values.…”
Section: Discussionmentioning
confidence: 91%
“…The period when the highest residue level was reported was fall/winter, and the reason the authors attributed to the fact was that plants subject to pesticides in summer periods were given to animals during the winter period. 41 In the present study, data was collected during the summer period when pesticide application is more common. All of the mothers in whom breast milk residue was detected resided in the agricultural area.…”
Section: Discussionmentioning
confidence: 99%
“…Fagnani et al (2011) estudaram a contaminação do leite no agreste Pernambucano e as amostras analisadas apresentaram elevada incidência de organofosforados e carbamatos. Na Itália Pagliuca et al (2006) determinaram resíduos de organofosforados em leite cru, sendo que o clorpirifós e acefato foram os compostos encontrados com maior frequência.…”
Section: Análise Cromatográficaunclassified